Eczema and water hardness: another piece of the puzzle found?. (29th January 2020) - Arents, B.W.M.; Leonardi‐Bee, J.
Abstract : Linked Article:  Jabbar‐Lopez et al . Br J Dermatol 2020; 183:285–293 .